(untitled) (Indian Journal of Nematology, 2025)
This study aimed to investigate the nematode diversity in various cropping systems across five districts (Aizawl, Kolasib, Mamit, Serchhip and Champhai) of Mizoram, India. The study revealed the presence of 11 nematode orders, encompassing 35 families and 70 genera. Among the 70 genera, 14 belong to the order Tylenchida, 2 to Aphelenchida, 26 to Dorylaimida, 1 to Mononchida, 15 to Rhabditida, 3 to Araeolaimida, 1 to Monhysterida, 4 to Triplonchida, 2 to Enoplida, 2 to Plectida, and 1 to Isolaimiida. Important plant parasitic nematode (PPN) genera included Meloidogyne (M. incognita, M. javanica), Pratylenchus (P. coffeae, P. zeae), Rotylenchulus (R. reniformis), Hirschmanniella (H. oryzae, H. mucronata), Tylenchorhynchus (T. mashhoodi), Helicotylenchus (H. dihystera, H. multicinctus), Hoplolaimus (H. indicus), Criconemoides, Hemicriconemoides, Xiphinema, and Longidorus. The distribution of economically important PPNs was visualized using a thematic spatial distribution map along with the population density of nematode abundance. Our study demonstrates that root-knot nematodes could be a potential threat to the vegetable cropping system in Mizoram. To our knowledge, this study will generate baseline information on economically important PPNs, which could help assess biological soil health scenarios, and identify the likely risk of growing crops in the area.